Cuentas por cobrar de los tributos municipales del Gobierno Autónomo Descentralizado del Cantón Vinces en el periodo 2023. - León Sánchez, Higol Armando (2024)
The case study "Accounts Receivable of Municipal Taxes of the Decentralized Autonomous Government of the Canton Vinces in the 2023 period" addresses the issue of efficient management of municipal taxes, a critical aspect in local public administration. This study is justified by the need to identify and analyze deficiencies in collection policies that influence the liquidity of the GAD of Vinces. The main objective is to evaluate the state of accounts receivable for municipal taxes by reviewing the tax records of the GAD during 2023, analyzing collection efficiency through financial indicators, and determining their impact on the entity's liquidity. The methodology employed includes a mixed approach, combining quantitative analysis of financial indicators with an-interview, in addition to a documentary review of accounting records. The results reveal a significant decrease in the liquidity index from 2.84 in 2022 to 1.49 in 2023, along with an increase in the delinquency rate and an extension of the average collection period, indicating inefficiencies in these areas. The conclusions indicate that these issues have affected the GAD's ability to finance public projects.